Abdominal Wall Desmoid during Pregnancy: Diagnostic Challenges - Johnny Awwad; Nadine Hammoud; Chantal Farra; Farah Fares; George Abi Saad; Ghina Ghazeeri (Case Reports in Obstetrics and Gynecology)
Background. Desmoids are benign tumors, with local invasive features and no metastatic potential, which have rarely been described to be pregnancy associated. Case. We described the rapid growth of an anterior abdominal wall mass in a 40-year-old pregnant woman. Due to its close proximity to the enlarged uterus, it was misdiagnosed to be a uterine leiomyoma by ultrasound examination. Final tissue diagnosis and radical resection were done at the time of abdominal delivery. Conclusion. Due to the diagnostic limitations of imaging techniques, desmoids should always be considered when the following manifestations are observed in combination: progressive growth of a solitary abdominal wall mass during pregnancy and well-delineated smooth tumor margins demonstrated by imaging techniques. This case emphasizes the importance of entertaining uncommon medical conditions in the differential diagnosis of seemingly common clinical manifestations.